Climate change, scenarios and their impact on potato diseases - Kaukoranta, Timo (MTT, 2007)
Since 1970 s Europe has warmed rapidly, more than observed globally. The warming may partially result from inherent variation of climate but its rate and geographical distribution fits the expected pattern of global climate change. The observed rate of warming is comparable to the expected rate in the next decades. Over the 21st century climate is expected to become gradually milder and more humid in Northern Europe and hotter and more arid in the South; Central Europe is becoming warmer with more extreme weather events; CO2 concentration continues to rise steadily. Global climate scenarios suggest that warming until mid-century is already largely determined and only after mid-century the outcome of climate change could be significantly affected by policy decisions and economic development. In some areas in Europe the warming in the past 30 years is so large that trends of seasonal temperature parameters are discernible. If statistics on pest occurrence or multiplication rate exist in these areas, it may be possible to attribute statistically part or all of the changes in pest dynamics to the observed climatic changes. Regional climate scenarios extend knowledge of the climate to future decades and provide daily weather data for modelling pest dynamics in future conditions. Repeating model runs over years gives an estimate of a probability distribution of pest risk. If pest risk is cumulative over years or shows lag after a climate threshold has been crossed, each of individual runs requires special consideration in setting initial values or climate data over several years. It is possible to generate hourly weather data for any particular site and period in future, which allows simulation of future local epidemics. However, these data represent only one possible set of climate conditions and it is difficult to explore the entire range of climate conditions. Another way of representing climate is to compute the combined distribution of climate parameters e.g. number of rain days, daily minimum temperature, and daily temperature range in future by extrapolating statistically from past climate data or from the daily output of regional climate models. If observed pest response to climate can be related to these parameters, the model can be used for deriving estimates of change of pest risk as climate changes. All predictions of future pest risk are conditional to the assumption that pest response to climate and interactions with host, soil, and surrounding environment are stable. Knowing that this assumption cannot always be true it seems useless to extend pest risk predictions beyond a few decades. Yet, over a few decades climatic variation can be larger than the general warming trend in any particular region. This makes it difficult to reach results that would be valuable for potato industry and supporting research. The value of studying the effect of climate change on potato pests lies in detecting ongoing changes of pest risks and understanding their origin, which is useful for planning pest control under the current climate.
Keywords: Ka; Climate change; disease; regional climate scenario